2006
DOI: 10.3892/or.16.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dysregulated genes in cutaneous squamous cell carcinoma

Abstract: Carcinogenesis is a multi-step process resulting from the accumulation of genetic mutations and subsequently leading to dysregulated genes, but the number and identity of differentially expressed genes in cutaneous squamous cell carcinoma (SCC) is unknown at present. In order to identify dysregulated genes, we examined the relative mRNA expression present in cutaneous SCC and its precursor lesion actinic keratosis (AK) by comparison to normal skin. Snap frozen biopsies from 20 specimens of normal skin, 10 AK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 35 publications
4
49
0
1
Order By: Relevance
“…Several proteins found here to have higher abundances in cSCC tumor sections, were previously reported at higher levels in cSCC lesions using antibody-dependent methods, such as immunohistochemistry and western blots. Such proteins include TNC (12,25), IQGAP1 (51) and S100A2 (52). On the other hand, changes in proteins, such as S100A11, ANXA1, RPS8, RPS4X, FSCN1, MYH9, ARG1 and CST6, which play roles in various carcinogenic processes (53-60), were not previously reported in cSCC, and our study is the first to show such associations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several proteins found here to have higher abundances in cSCC tumor sections, were previously reported at higher levels in cSCC lesions using antibody-dependent methods, such as immunohistochemistry and western blots. Such proteins include TNC (12,25), IQGAP1 (51) and S100A2 (52). On the other hand, changes in proteins, such as S100A11, ANXA1, RPS8, RPS4X, FSCN1, MYH9, ARG1 and CST6, which play roles in various carcinogenic processes (53-60), were not previously reported in cSCC, and our study is the first to show such associations.…”
Section: Discussionsupporting
confidence: 52%
“…One of the most prominent contributing factors to poor patient outcome is the lack of sensitive biomarkers to facilitate early diagnosis and management of the tumor. A handful of genetic biomarkers have been studied in cSCC, including cellular tumor antigen p53 (TP53), notch 1 (NOTCH1) (6,7), human epidermal growth receptor 2 (HER2), HER4, E-cadherin (CDH1), epidermal growth factor receptor (EGFR), and podoplanin (PDPN) (5,8,9), and some have shown potential for prognostication (9)(10)(11)(12). However, there is a lack of evidence to recommend the use of these biomarkers for cSCC tumor stratification.…”
mentioning
confidence: 99%
“…Several genes involving the TP53 pathway, anti-apoptotic pathways, signal transduction, structural loss and DNA replication, including BCL2A1, MUC4, PTPN11 (SHP2) and FGF9, were confirmed upregulated in SCC and suggested to be warranted further study regarding their role in disease pathogenesis (Kathpalia et al, 2006). CNN2, COX4l1, COX5B, COX7C, CRLF3, CTSC showed increased expression (Dang et al, 2006). In cSCC.Matrix metallopeptidase 13 (MMP13) was identified as a direct target suppressed by miR-125b (Xu et al, 2012).…”
Section: Abnormally Expressed Genes In Csccmentioning
confidence: 97%
“…Analysis of IRF6 expression in a large series of SCCs showed a strong down-regulation that correlated with tumor invasive and differentiation status (Botti et al, 2011). RPL15 and LGTN were down-regulated and the expression of p15(INK4b) was significantly reduced (Dang et al, 2006;Moad et al, 2009). The expression of KGF receptor (KGFR) mRNA was lower in cutaneous SCCs than in normal skin samples (Toriseva et al, 2012).…”
Section: Abnormally Expressed Genes In Csccmentioning
confidence: 99%
“…Several mRNA biomarkers for cSCC were identified, including CCR10, CCL27, MUC4, p16, MMP2 and MMP9. (61) A recent study has demonstrated that a distinct microRNA profile is modulated by UV radiation. (62) …”
Section: Rna and Mirnamentioning
confidence: 99%